Exercise Systolic Reserve and Exercise Pulmonary Hypertension Improve Diagnosis of Heart Failure With Preserved Ejection Fraction - Verwerft, Jan; Verbrugge, Frederik H.; Claessen, Guido; Herbots, Lieven; Dendale, Paul; Gevaert, Andreas B. (Frontiers in Cardiovascular Medicine, 2022)
Aims Diastolic stress testing (DST) is recommended to confirm heart failure with preserved ejection fraction (HFpEF) in patients with exertional dyspnea, but current algorithms do not detect all patients. We aimed to identify additional echocardiographic markers of elevated pulmonary arterial wedge pressure during exercise (exPAWP) in patients referred for DST. Methods and Results We identified candidate parameters in 22 patients referred for exercise right heart catheterization with simultaneous echocardiography. Elevated exPAWP (≥25 mmHg) was present in 14 patients, and was best identified by peak septal systolic annular velocity <9.5 cm/s (exS’, area under the receiver operating characteristic curve (AUC) 0.97, 95% confidence interval 0.92-1.0) and mean pulmonary artery pressure/cardiac output slope ≥3.2 mmHg/L (mPAP/CO, AUC 0.88 [0.72-1.0]). We propose a decision tree to identify patients with elevated exPAWP. Applying this decision tree to 326 patients in an independent non-invasive DST cohort showed that patients labeled as ‘high probability of HFpEF’ (n=85) had reduced peak oxygen uptake (13.0 [10.7-15.1] mL/kg/min, p<.001 vs intermediate/low probability), high H2FPEF score (53 [40-72]%, p<.001 vs intermediate/low probability), and typical clinical characteristics. The diagnostic yield of DST increased from 11% using exercise E/e’, to 62% using the decision tree. Conclusion In DST for suspected HFpEF, exS’ was the most accurate echocardiographic parameter to identify elevated PAWP. We propose a decision tree including exS’ and mPAP/CO for interpretation of DST. Application of this decision tree revealed typical HFpEF characteristics in patients labeled as high probability of HFpEF, and substantially reduced the number of inconclusive results.